IMPLIKASI FILSAFAT KRITISISME IMMANUEL KANT BAGI PENGEMBANGAN STUDI HUKUM EKONOMI SYARIAH - Wibawa, Ginan; Rizal Muttaqin (Humantech : Jurnal Ilmiah Multidisiplin Indonesia, 2021)
Sharia economic law (fiqh muāmalah) is the main instrument in thedevelopment of contemporary Islamic financial institutions. However, in itsapplication, there are still various kinds of problems that indicate thedominance of the ideological-normative paradigm rather than the empiricalobjective paradigm. This paper aims to unravel this problem by looking atthe implications of Immanuel Kant's philosophy in the development ofsharia economic law studies. The method used in this paper is a method of studying documentation and literature which is closely related to the object ofstudy and other references in the form of the results of previous research andtheories from v arious textbooks and analyzed with a philosophical andhistorical approach. This article finds that Kant's philosophy of criticism beginsby placing doubts on the philosophy of rationalism which accepts a prioriknowledge without criticism. But not as skeptical as Hume, Kant tried toformulate an epistemology that would allow this a priori knowledge to beaccepted. Until finally Kant found an a priori synthesis of knowledge thatbridges between rationalism and empiricism. Therefore, herein lies theurgencyof Kant's epistemological influence on the development of the study of Islamiceconomic law which tries to formulate the idea of the importance of combiningideologyand theory, between normative-idealist and historical-empirical. Thus,Islamic teachings formulated in Islamic economic law and implemented inIslamic financial institutions, with their complementary and supplementarynature, can be an instrumentfor building a value-based economic and financialsystem.